Life and Pastoral Ministry of Fr. Jan Góra, OP (1948–2015) - Orzechowski, Rafał (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The life and ministry of Father Jan Góra, OP (d. 2015), were marked by a persistent desire to bear witness to Jesus Christ. His profound inner relationship with the Teacher from Nazareth has consistently transferred into external action—often of nationwide significance. The study entitled Youth and Pastoral Ministry of Father Jan Góra (1948–2015) is structured as a triad comprising: “youth and vocational discernment,” “places and character of ministry,” and “three daughters: Hermanice, Jamna, and Lednica.” This framework allows for a comprehensive understanding of Father Góra’s person and mission. The analysis leads to the conclusion that his life exhibits a notable continuity, which may rightly be interpreted as the work of divine providence.